Fabrication of hierarchically porous structured PDMS composites and their application as a flexible capacitive pressure sensor. (15th April 2021) - Hwang, Juwon; Kim, Yeongjun; Yang, Hyeondong; Oh, Je Hoon
Abstract: Pressure sensors for wearable electronics are mounted on irregular surfaces and exposed to various external stimuli. Therefore, the sensor should have a flexible structure and wide pressure measurement range along with high sensitivity. In this study, we fabricated hierarchically porous structured polydimethylsiloxane (PDMS) composites with a simple and cost-effective method using sugar particles and a water-in-oil emulsion. Hierarchically porous PDMS composites were employed as the dielectric layers of flexible capacitive pressure sensors. The capacitive pressure sensor presents a sensitivity 22.5 times higher (0.18 kPa −1 ) than the sensors using bulk PDMS with a wide measurement range (0–400 kPa). The finite element analysis was implemented to analyze the non-linearity of sensors by observing the compressive behavior of the PDMS composites. For the practical applications, finger attached-sensor, respiration monitoring system, and sensor array were tested, and the proposed sensors showed sufficient potential for application in wearable electronics.